EXPLORING THE IMPACT OF AGRIBUSINESS DEVELOPMENT ON RURAL LIVELIHOODS IN BAMENDA II MUNICIPALITY, CAMEROON - NDOFOR, AKWO; FORJI, EFEUTLANCHA (FEB - Universitas Lampung, 2025)
The sustainable rural livelihoods approach is one of the new analytical approaches in the arena of agribusiness development and is considered much in recent years to achieve rural livelihoods and poverty reduction. This study aimed to explore the impact of agribusiness development on rural livelihoods in Bamenda II Municipality, Cameroon. The study utilized a descriptive research design. The study used a survey method for data collection. Data was collected from individual farmers in Bamenda II municipality. The self-administered questionnaire method was used to collect data from the participants. Simple random sampling methods were used, and the sample size of 99 participants was determined using Cochran Fomulae. Descriptive statistics were used for data analysis using SPSS version 21. The findings revealed that there is a positive and statistically significant relationship between agricultural production and rural livelihoods. A one-unit increase in agricultural production is associated with a 0.765-unit increase in rural livelihoods, while a one-unit increase in market access is associated with a 0.517-unit increase in rural livelihoods. The positive relationship between market access and rural livelihoods is statistically significant at the 1% level. However, the relationship between employment creation and rural livelihoods is positive but statistically insignificant. A one-unit increase in employment creation is associated with a 0.038-unit increase in rural livelihoods, but the relationship is not statistically significant at the 10% level. To conclude, these findings have important implications for policymakers and development practitioners working to enhance the well-being of rural communities. Investing in agricultural productivity, as well as improving market access and infrastructure, can be effective strategies for promoting sustainable rural livelihoods and reducing poverty